Needs of family caregivers of the patients with Alzheimer disease: Analyzing of family caregivers experiences - Mohammadi, Farahnaz; Fallahi khoshknab, Masoud; khanke, Hamid Reza (Advances in Nursing & Midwifery, 2012)
Needs of family caregivers of the patients with Alzheimer disease: Analyzing of family caregivers experiences Mohammadi F 1 (PhD), Fallahi khoshknab M 2 (PhD), khanke H3 (PhD) 1. Assistant Professor, Dept of Gerontology & Research Center on Aging, Social Welfare and Rehabilitation Sciences University, Tehran, Iran. 2. Assistant Professor, Dept of Nursing, Social Welfare and Rehabilitation Sciences University, Tehran, Iran. 3. Assistant Professor, Dept of Nursing, Social Welfare and Rehabilitation Sciences University, Tehran, Iran. Abstract Background and aim With the increasing elder population, providing effective family care is turning to be the most important challenge in health and welfare of elder people. The aim of this study was to explore needs of family caregivers of the patients with Alzheimer disease by analyzing of family caregivers experiences Materials and methods This qualitative study was conducted by latent conventional content analysis. 35 family caregivers of elder patients with Alzheimer disease participated in the study. Participants were selected based on purposive sampling. Sources of information included documents of participant's diaries, about their problematic and complicated days of caring. Data were analyzed through reading and rereading documents, determining meaning units, extracting of codes and categorizing of them. Findings Most of participants (80%) were female, with mean age of 56/2 and literate (under diploma level). The findings generated 794 initial codes, which were grouped in 7 categories of: need to knowledge, receiving help from other family members in caring, modification of the home environment, self caring of caregivers, need "to be visible", compatible and complimentary health care system and caring equipments. Conclusion Regarding to Global expansion of Alzheimer disease, considering the family care giving issue of elders with Alzheimer disease is essential. Therefore, providing suitable information, establishing education for caregivers related to disease and patient care management, management of caregivers’ health, psych–social support and establishing of appropriate complimentary health care system for elderly patients should be considered. These strategies would facilitate the family care giving and support the caregivers on their journey. Keywords: Elderly, Alzheimer, Need, Family caregiver *Corresponding Author: Farahnaz Mohammadi, Assistant Professor at Social Welfare and Rehabilitation Sciences University, Department of gerontology & Research center on Aging. E-mail: f.mohammadi@uswr.ac.ir